2013
DOI: 10.1111/jvim.12270
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adipokine Concentrations in Dogs with Naturally Occurring Pituitary‐Dependent Hyperadrenocorticism

Abstract: BackgroundAn excess of intra‐abdominal fat is observed frequently in dogs with hyperadrenocorticism (HAC). Adipokine dysregulation is a possible cause of complications related to visceral obesity, but little information is available on adipokine in dogs with naturally occurring HAC.ObjectivesTo examine the differences in the circulating adipokines concentrations in overweight dogs with and without pituitary‐dependent HAC (PDH).AnimalsThirty healthy dogs and 15 client‐owned dogs with PDH.MethodsCase–controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 48 publications
1
33
1
1
Order By: Relevance
“…Therefore, it was hypothesized that leptin concentrations would be even higher in patients with both GBM and an endocrinopathy compared to those with only 1 disease but this was not the case in the our study. The association between leptin and endocrinopathies as well the association between leptin and GBM has been identified in several previous studies . Accordingly, we expected to observe a higher serum leptin concentration in GBM patients with concurrent endocrinopathy than in cases of either disease alone but this synergistic effect of GBM and endocrinopathies on leptin concentration could not be clearly identified in our study.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Therefore, it was hypothesized that leptin concentrations would be even higher in patients with both GBM and an endocrinopathy compared to those with only 1 disease but this was not the case in the our study. The association between leptin and endocrinopathies as well the association between leptin and GBM has been identified in several previous studies . Accordingly, we expected to observe a higher serum leptin concentration in GBM patients with concurrent endocrinopathy than in cases of either disease alone but this synergistic effect of GBM and endocrinopathies on leptin concentration could not be clearly identified in our study.…”
Section: Discussionmentioning
confidence: 44%
“…Previous studies have suggested that leptin has a synergistic interaction with endocrinopathies such as hyperadrenocorticism, hypothyroidism, and diabetes mellitus, which were associated with increased leptin concentrations . In addition, a case–control study showed that these endocrinopathies were associated with GBM; in particular, the presence of hyperadrenocorticism increased the morbidity of GBM 29‐fold .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A canine‐specific ELISA for total adiponectin is available for use and a negative correlation with body condition score ( r = −0.446, P < .01; n = 100) has been reported in dogs . There was no difference in total adiponectin concentrations when overweight dogs with and without pituitary‐dependent hyperadrenocorticism were compared, but lower total adiponectin concentrations were detected in dogs with newly diagnosed diabetes mellitus, compared with healthy dogs in horses . Additional research is required to determine whether HMW adiponectin concentrations are altered by management changes and medical treatments for ID.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve intact bitches were also excluded. At follow‐up after AP treatment, 4 dogs were removed from the study because of hyperadrenocorticism, which has been reported to affect circulating adipokines concentrations . Thus, 25 dogs with AP were included in this study.…”
Section: Methodsmentioning
confidence: 99%